Eculizumab and refractory membranoproliferative glomerulonephritis - Radhakrishnan, Seetha; Kirschfink, Michael (The New England journal of medicine, 2012)
This letter to the editor discusses the use of eculizumab in refractory membranoproliferative glomerulonephritis. The response appears to be dramatic.